Exploring factors influencing parents’ adoption intention toward children’s illustrated e-books: A push-pull model perspective - Lufei Guan; Wenbo Wei; Mengxi Fu (PLoS ONE, 2026)
With the development of multimedia technologies, children’s illustrated e-books are getting increasingly popular due to their diverse formats and engaging content. However, few studies have explored the factors influencing parents’ adoption intention toward illustrated e-books for children. This research aims to address this gap by employing the push-pull model to explore the influences of pull factors (i.e., relative advantages, perceived trialability, perceived enjoyment, variety-seeking), push factors (i.e., vision health stress, evaluation cost), and individual characteristics (i.e., age, gender, experience of use) on parents’ adoption intention toward illustrated e-books for children. Data were collected from 348 parents in China and analyzed using structural equation modeling (SEM). The research results suggest that perceived enjoyment and variety-seeking are important pull factors, while evaluation cost serves as a vital push factor. Moreover, children’s gender significantly influences the adoption intention. Parents of boys demonstrated a higher adoption intention than parents of girls. These nuanced insights have practical implications for designers of illustrated e-books for children.